2010
DOI: 10.1158/0008-5472.can-09-3704
|View full text |Cite
|
Sign up to set email alerts
|

SuperiorIn vivoEfficacy of Afucosylated Trastuzumab in the Treatment of HER2-Amplified Breast Cancer

Abstract: The enhancement of immune effector functions has been proposed as a potential strategy for increasing the efficacy of therapeutic antibodies. Here, we show that removing fucose from trastuzumab (Herceptin) increased its binding to FcγRIIIa, enhanced antibody-dependent cell-mediated cytotoxicity, and more than doubled the median progression-free survival when compared with conventional trastuzumab in treating preclinical models of HER2-amplified breast cancer. Our results show that afucosylated trastuzumab has … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
166
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 199 publications
(179 citation statements)
references
References 37 publications
(44 reference statements)
12
166
1
Order By: Relevance
“…3. No effect of Ox or fucosylation degree of IgG was measured on FcγRI binding, confirming earlier results in the literature on FcγRI binding for oxidized IgG1 20 and fucosylation 17, 18.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…3. No effect of Ox or fucosylation degree of IgG was measured on FcγRI binding, confirming earlier results in the literature on FcγRI binding for oxidized IgG1 20 and fucosylation 17, 18.…”
Section: Resultssupporting
confidence: 89%
“…Furthermore, fucosylation levels of the antibody have an impact on the binding to FcγRIIIa and FcγRIIIb, whereas no differences in binding were measured on any of the other Fc receptors. These results are in agreement with the literature 13, 16, 17, 18, 19. None of the cited references studied the effect of DG on fraction bound at neutral pH, and we have demonstrated that there is a significant impact.…”
Section: Discussionsupporting
confidence: 93%
“…It is known that mouse FcγRs and FcRn efficiently bind human IgG subclasses, but the affinity is lower than that of the human versions, so humanized antibody Fc cannot effectively activate NK cells and macrophages of BALB/c nude mice compared with mouse IgG subclasses. 23 However, the ADCC function of MBS301 can be observed in the humanized mice (hu-CD34 NSG mice) study (Figure 7c); there was a slight visible difference between the MBS301 and MBS301 + F groups in tumor inhibition and the recurrence ratio of MBS301 was lower than that of MBS301 + F. 24 Still, the content of humanized NK cells was much lower in hu-CD34 NSG mice than in human. 25 The NK cells could account for 5–20% in human peripheral blood mononuclear cells; thus, significant ADCC function for killing cancer cells could be observed for MBS301 when used as a treatment in humans.…”
Section: Discussionmentioning
confidence: 93%
“… 132 Humanized IgG1     Bemarituzumab /FPA144FGFR2bafucosylatedFUT8 −/− CHO cells (Potelligent® Technology)Enhanced tumour growth inhibition in FGFR2-overexpressing gastric cancer xenograft mouse model over isotype control(b)Humanized IgG1     Afucosylated TrastuzumabHER2afucosylatedFUT8 −/− CHO cells (Potelligent® Technology)Enhanced tumor growth inhibition over fucosylated trastuzumab in KPL-4 xenografts in human FcγRIIIα miceJunttila et al. 133 Humanized IgG1     TrasGEX/ GT-MAB7.3-GEX/Glycooptimized Trastuzumab-GEXHER2ReducedHuman glycoengineered production cell lines (GlycoExpress technology)Potent Her2 + BT474 tumor growth inhibition in nude mice but exhibited similar tumor volume and number of regression between fucosylated and reduced fucosylated antibodies(c)Humanized IgG1     Lumretuzumab /RG7116/RO5479599/ GE-HuMAb-HER3HER3ReducedCoexpression with GnT-III and α-ManII in CHO cells (GlycoMAb Technology)Enhanced survival of SCID-beige mice with A549-B34 NSCLC xenograftsMirschberger et al. 134 Humanized IgG1   Enhanced tumor inhibition in A549 orthotopic mouse models over WT-huMab-HER3 Palivizumab-NRespiratory syncytial virus (RSV)afucosylatedTransgenic N. benthamiana with RNAi to eliminate the expression of plant specific xylosyl and fucosyl transferase genesEnhanced RSV protection in rat models over fucosylated counterpart(d)…”
Section: Enhanced Adcc Activities By Afucosylated Antibodies In In VImentioning
confidence: 99%